2015
DOI: 10.1128/jcm.00864-15
|View full text |Cite
|
Sign up to set email alerts
|

Testing Pooled Sputum with Xpert MTB/RIF for Diagnosis of Pulmonary Tuberculosis To Increase Affordability in Low-Income Countries

Abstract: Tuberculosis (TB) is a global public health problem, with the highest burden occurring in low-income countries. In these countries, the use of more sensitive diagnostics, such as Xpert MTB/RIF (Xpert), is still limited by costs. A cost-saving strategy to diagnose other diseases is to pool samples from various individuals and test them with single tests. The samples in positive pool samples are then retested individually to identify the patients with the disease. We assessed a pooled testing strategy to optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 14 publications
3
36
0
2
Order By: Relevance
“…However, the few studies which have been published on this approach show its promise. A study evaluating the pooled Xpert testing strategy in Nigeria showed that it would have identified 96% of individual specimens containing TB bacteria and could have reduced Xpert costs and usage by 30% [19]. Another evaluation in South Africa showed that Xpert identified 100% of pools containing AFB smear-positive specimens, but just 76% of pools with AFB smear-negative, culture-positive specimens [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the few studies which have been published on this approach show its promise. A study evaluating the pooled Xpert testing strategy in Nigeria showed that it would have identified 96% of individual specimens containing TB bacteria and could have reduced Xpert costs and usage by 30% [19]. Another evaluation in South Africa showed that Xpert identified 100% of pools containing AFB smear-positive specimens, but just 76% of pools with AFB smear-negative, culture-positive specimens [20].…”
Section: Introductionmentioning
confidence: 99%
“…Dentre outros pontos citados como desfavoráveis, podem ser observados: o custo, que impossibilita, por muitas vezes, a repetição dos testes 37,57,58,59 ; a detecção de falso-positivos e falsonegativos durante o estudo 49 ; o número de erros e resultados inválidos; as amostras com volume insuficiente (menos de 1 mL); e as amostras que apresentam vestígios de sangue pesados ou resíduos de alimentos e têm que ser examinadas por baciloscopia 46 .…”
Section: Discussionunclassified
“…These costs can quickly become prohibitively expensive in resource-poor settings (e.g. pathogen surveillance in developing countries [1,2], in non-human systems, such as wildlife disease surveillance [3]), or when reagents become scarce due to a rapid spike in testing demand (e.g. during the SARS-CoV-2 pandemic [4]).…”
Section: Introductionmentioning
confidence: 99%